Treatment burden in stage I seminoma: a comparison of surveillance and adjuvant radiation therapy. (13th August 2013) - Leung, Eric; Warde, Padraig; Jewett, Michael; Panzarella, Tony; O'Malley, Martin; Sweet, Joan; Moore, Malcolm; Sturgeon, Jeremy; Gospodarowicz, Mary; Chung, Peter
Abstract : Objective: To examine the management and outcomes of patients with stage I seminoma and to relate these to overall treatment burden. Patients and Methods: A total of 764 patients with stage I seminoma underwent surveillance or adjuvant radiation therapy (RT) at a single institution. First relapse on surveillance was managed with RT alone, or with combination chemotherapy (ChT) for more extensive recurrence. Second relapse was managed with ChT. Relapse after adjuvant RT was treated with ChT. The treatment burden was measured, according to the specific treatment undertaken after orchiectomy, by defining treatment episodes as follows: surgery – one episode; one course of RT – one episode; one course of ChT – one episode. Results: In all, 484 patients underwent surveillance and 280 received adjuvant RT. The 5‐ and 10‐year overall survival rates were 98.6 and 97.7% for surveillance, and 97.2 and 91.4% for adjuvant RT. A total of 72 (15%) patients in the surveillance group relapsed; treatment for relapse was RT ( n = 56), ChT ( n = 15) and surgery ( n = 1). Second relapse occurred in six patients; these patients were treated with ChT. Of the patients in the adjuvant RT group, 14 (5%) relapsed: salvage treatment was 10 – ChT ( n = 10) surgery ( n = 1) and further RT ( n = 3). The overall treatment burden represented by number of treatment episodes per patient was 0.16 in the surveillance group and 1.05 in the adjuvant RT group. Conclusions: Surveillance reduces the overall treatment burden in patients with stage I seminoma and is the preferred management option. The selective use of RT at first relapse for patients on surveillance leads to a similar requirement for subsequent ChT to that for patients on adjuvant RT.